Increasing activeness and learning outcomes of mathematics using problem-based learning (PBL) in grade 2 SD Yos Sudarso Purwakarta - Hadiyanto, Fahrur Rozi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
the lecture style still dominates and the content does not match the actual situation, so the activity and learning outcomes of the 2nd-grade students of Yos Sudarso Elementary School for the 2022/2023 academic year are still not good. The overarching aim of this study is to outline how to introduce a Problem-Based Learning pedagogical framework to enhance student engagement and knowledge retention. This study followed the format of Classroom Action Research (PTK) in two cycles. This research involved 28 students from SD Yos Sudarso Purwakarta. Data collection methods, including test and nontest methods. Quantitative and qualitative descriptive analyzes were applied to the data. The results showed that the proportion of active students increased from 21.42 percent or as many as six students in the pre-cycle to 53.57 percent or as many as fifteen students in cycle I and to 78.57 percent or as many as twenty-two students, in the second cycle. The pre-cycle KKM achievement level was 53.57 percent (15 students), the first cycle achievement level was 78.57 percent (22 students), and at the second cycle achievement level all students achieved KKM scores of 28 students